Cyclic flexural tests of hybrid steel–precast concrete beams with simple connection elements. (1st July 2016) - Yang, Keun-Hyeok; Seo, Eun-A; Hong, Seung-Hyun
Highlights: This study developed a hybrid H-steel–precast concrete (HSPC) beam system. An innovative ductile connection for the HSPC beams was proposed. We revealed that the hybrid beam system with a bolt connection fails in brittle. We ascertained that the HSPC beams retain as much ductile as conventional RC beams. Abstract: A hybrid H-steel–precast concrete (HSPC) beam system with a simple ductile connection was developed to overcome the limitations of a conventional hybrid beam system with a bolt connection between the H-steel beams supported by columns and H-steel beams embedded into the concrete beams. The developed HSPC beam system has three different sections: H-steel, joint, and reinforced concrete sections. To examine the effectiveness on the moment resistance and ductile performance of the developed HSPC beam system, five fixed-end beam specimens were tested under reversed cyclic one-point concentrated top loads at mid-span. The prepared specimens were designed as follows: H1.0, H0.5, and H0.25 were used to evaluate the effect of the location of the joint on the flexural behavior of the developed HSPC beam; P0.5 was used to introduce the prestressing force; and S0.5 was used to examine the effect of the lap splices of the headed longitudinal reinforcing bars on the stress transfer at a joint. The flexural capacity of the fixed-end HSPC beams was evaluated based on the virtual work principle under the assumption of rigid joints at the connection of the steel and concrete beams. None of the beam specimens showed shear cracks or splitting tensile cracks around the joint region until the beam failed, unlike in the conventional hybrid beam system with a bolt connection. The developed HSPC beam retained a ductility comparable to that of conventional RC beams. From the measured crack propagation, cyclic load–displacement curve, consistency of the recorded strain distribution along the beam length with the calculations, and agreement between the ultimate loads and the calculated collapse loads, the proposed joint element connecting the H-steel and RC beams can be regarded as a rigid connection, resisting the applied moments.